The vibrant years : a novel - Dev, Sonali (Mindy's Book Studio, 2022)
"When sixty-five-year-old Bindu Desai inherits a million dollars, she's astounded--and horrified. The windfall threatens to expose a shameful mistake from her youth. Desperate to keep the secret, Bindu quickly spends it on something unexpected: a condo in a posh retirement community in Florida. The impulsive decision blindsides Bindu's daughter-in-law, Aly. At forty-seven, Aly still shares a home with Bindu even after her divorce from Bindu's son. But maybe this change is just the push Aly needs to fight for the segment she's been promised for years at the news station where she works. As Bindu and Aly navigate their new dynamic, Aly's daughter, Cullie, is faced with losing the business that made her a tech-world star. The only way to save it is to deliver a new idea to her investors--and of course they want the half-baked dating app she pitched them in a panic. Problem is, Cullie has never been on a real date. Naturally, enlisting her single mother and grandmother to help her with the research is the answer"--